ANTI-INFLAMMATORY EFFECT OF CARALLUMA EDULIS AGAINST ACUTE AND CHRONIC INFLAMMATION - A. M. Minhas; Arif-ullah Khan; M. M. Ansari (Journal of Animal and Plant Sciences, 2018)
Caralluma edulis (Edgew.) Benth. ex Hk.f. (Asclepiadaceae) is traditionally used for the management of rheumatism. The current study aimed to assess the anti-inflammatory effect of Caralluma edulis, to explain its medicinal use in inflammatory ailments. Caralluma edulis crude extract (Ce.Cr) was investigated in acute (carrageenan and xylene mediated) and chronic (formalin evoked) models of inflammation in mice. Ce.Cr  which shows the presence of alkaloids, glycosides, flavonoids, saponins, phenols, terpenes and tannins caused dose-dependent (100, 300 and 1000 mg/kg) reduction of the carrageenan, xylene and formalin-induced inflammation (P < 0.05, P < 0.001 vs. saline group). At the lower dose of 30 mg/kg it was effective in inhibiting the xylene mediated ear edema. No mortality observed with Ce.Cr upto 5 g/kg. This study reveals that Caralluma edulis possess therapeutic ability to reduce inflammation, hence proving its potential to be used as an alternative medicine in the management of inflammatory disorders and also validate its folkloric use in treatment of rheumatism.
Keywords: Asclepiadaceae; anti-inflammatory; Caralluma edulis; formalin; carrageenan